Comparative sequencing in the genus Lycopersicon. Implications for the evolution of fruit size in the domestication of cultivated tomatoes. - Nesbitt, T Clint (2002)
Sequence variation was sampled in cultivated and related wild forms of tomato at fw2.2--a fruit weight QTL key to the evolution of domesticated tomatoes. Variation at fw2.2 was contrasted with variation at four other loci not involved in fruit weight determination. Several conclusions could be reached: (1) Fruit weight variation attributable to fw2.2 is not caused by variation in the FW2.2 protein sequence; more likely, it is due to transcriptional variation associated with one or more of eight nucleotide changes unique to the promoter of large-fruit alleles; (2) fw2.2 and loci not involved in fruit weight have not evolved at distinguishably different rates in cultivated and wild tomatoes, despite the fact that fw2.2 was likely a target of selection during domestication; (3) molecular-clock-based estimates suggest that the large-fruit allele of fw2.2, now fixed in most cultivated tomatoes, arose in tomato germplasm long before domestication; (4) extant accessions of L. esculentum var. cerasiforme, the subspecies thought to be the most likely wild ancestor of domesticated tomatoes, appear to be an admixture of wild and cultivated tomatoes rather than a transitional step from wild to domesticated tomatoes; and (5) despite the fact that cerasiforme accessions are polymorphic for large- and small-fruit alleles at fw2.2, no significant association was detected between fruit size and fw2.2 genotypes in the subspecies--as tested by association genetic studies in the relatively small sample studied--suggesting the role of other fruit weight QTL in fruit weight variation in cerasiforme.